Quantifying Microglial Phagocytosis of Apoptotic Cells in the Brain in Health and Disease. (24th May 2018) - Beccari, Sol; Diaz‐Aparicio, Irune; Sierra, Amanda
Abstract: Apoptosis is a ubiquitous process occurring in the brain under both physiological and pathological conditions. The central nervous system (CNS) requires an active and efficient clean‐up system to prevent the spillover of intracellular contents into the surrounding parenchyma and suppress the initiation of inflammatory and immune responses. Microglia, the resident professional phagocytes of the brain, are the cells in charge of the removal of these dead cells by the process named phagocytosis. Therefore, microglial phagocytosis is a vital mechanism to maintain tissue homeostasis. Traditionally, this process has been assessed using indirect methods, which have resulted in poor or inaccurate estimations of microglial phagocytosis efficiency. In these protocols, we describe a series of parameters to directly quantify microglial phagocytosis efficiency in vivo and in vitro. © 2018 by John Wiley & Sons, Inc.